Advocate Immunity Rights in Providing Legal Services to Clients - Yohanes Pande; Zakiyatun Nufus; Patawari Patawari; Rica Gusmarani; Muchamad Taufiq (Universitas Muhammadiyah Palu, 2024)
An advocate is a person whose profession is to provide legal services, both inside and outside the court, who fulfill the requirements under the Advocate law. Advocates are law enforcers, free and independent, guaranteed by laws and regulations.